The Existence and Fund Management of Indigenous Dayak Taman Community in Sibau Hilir Village from Legal Perspective - Puspita, Riza; Sari, Devina Puspita (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Fund management is one of the strategies carried out to maintain the cultural heritage of the Dayak tribe, especially the Taman Kapuas Dayak. However, along with changing times and modernization, the challenges in managing funds are increasingly complex. Problems such as lack of transparency, accountability and community participation are issues that need attention. In this context. This research aims to dig deeper into how Dayak indigenous community funds are managed and distributed. The research method used in this research is descriptive empirical juridical research. The results of this research are based on field facts obtained from direct interviews, then they will be described in detail and analyzed qualitatively. The results of this analysis will be expressed in written form sourced from primary and secondary data. Research findings show that the management and distribution of Dayak traditional community funds is carried out by the traditional head as the sole role in the traditional institution. Traditional leaders have an important role in managing and distributing traditional funds in their territory. The source of these customary funds comes entirely from the government. The distribution of funds to indigenous communities is carried out through the implementation of traditional rituals where the funds come from voluntary donations from indigenous communities and customary treasuries. This shows the differences in fund management systems in traditional institutions and business entities. The main difference lies in the obligations of the community/members. In traditional institutions there is no obligation for the community to spend their funds, whereas in business entities there is an obligation for members to carry out mandatory contributions. The big challenge currently faced is maintaining cultural heritage in light of the many social changes that are occurring and customs outside the traditional environment that are starting to influence local cultural customs.